Accurate calculation of the slip factor of axial cascades and impellers for arbitrary blade shapes - Smith, Henrik; Semel, Matthias; Epple, Philipp; Bleiziffer, Mihai; Delgado, Antonio (Proceedings of the ASME Turbo Expo, 2011)
Nowadays, design, redraft and optimisation strategies of axial fans often still rely on the one dimensional mean line theory. However, as it is well known, it is based on a number of assumptions that do not apply to real flow behaviour so that various deviations can be observed. In the present paper, the plane potential theory is used to examine and calculate these deviations. The behaviour of axial cascades is analysed in general and a slip factor is computed. On this basis a quasi-3D calculation method is developed. It is applied to an exemplary impeller and the results are compared with 3D CFD computations. The main characteristic figures are presented and different angle correction and angle exaggeration methods are investigated and compared. Finally, the applicability of the presented method to a precise axial fan design process is illustrated. Copyright © 2011 by ASME.
UnivIS-Import:2017-01-09:Pub.2011.tech.ITC.stmmec.accura